Modification of the weld penetration characteristics in laser deep welding using instationary gas flows / B. John ... [et al.] - B., John; F., Maqbool; D., Kowerko; J., Buhl; Hartel, Sebastian; J., Hensel (Smart Manufacturing Research Institute (SMRI), 2022)
The present report focuses on the integration of technology for generating temporally alternating (pulsed) gas flows in the field of laser welding. The technical realization requires specific adaptation of three core elements of the gas pulse system (valve, section of measurements, control system) to realize new parameters of laser welding. These parameters allow for a positive influence on the joining process and on the results of welding, respectively. By means of temporal control of the gas volume flow in combination with the laser welding process, it was possible to produce a force effect on the molten pool and subsequently to improve the characteristics of laser-welded seams-up to10% narrower, deeper at the same welding speed and laser power. The effects occurring through the use of instationary gas flow were evaluated by using the "classically" metallography and through the use of digital image processing. In parallel, the effect of pulsating gas flow on the melting zone was simulated by using specific software in order to make further statements about the effects.